Komponen Sistem Pengendalian Internal pada Badan Amil Zakat Nasional (BAZNAS) - Supandi Rahman (Jurnal Ekonomi Islam, 2022)
This study aims to evaluate the application of the internal control system in the management of zakat at the National Amil Zakat Agency of Gorontalo Regency. Models and data analysis techniques using descriptive methods and gap analysis, namely by analyzing/evaluating the gap between the implementation of the components of the internal control system of the Zakat Management Organization (OPZ), which consists of the availability of organizational structure, availability of job descriptions, job rotation and periodic leave, availability of documents with printed numbers, availability of separate special accounting divisions, availability of internal auditors, financial statements audited by public accountants. The results show that the internal control system in BAZNAS Gorontalo Regency has been mostly implemented. As for some components that have not been implemented, this is due to understandable reasons.